Advocating a rational use of self-confrontation micro-phenomenological interviews to improve performance in elite athletes - Terrien, E.; Leblanc, M.; Saury, J.; Hauw, D.; Huet, B. (Frontiers in Sports and Active Living, 2024)
Self-Confrontation Micro-Phenomenological Interviews (SCMPIs) aim to capture the fine-grained details of an athlete's experience, focusing on pre-reflective consciousness without resorting to post-hoc rationalizations. This specific type of self-confrontation interview was developed in the domain of work analysis in cognitive ergonomics. Despite its integration into numerous research studies in sport performance and training practices, the direct effects of the SCMPI on athletes remain underexplored. In this perspective article, we provide a brief overview of the theoretical foundations of SCMPI as well as a description of the paradox of the SCMPI situation. Throughout this paper, we highlight the unsolved questions around use of SCMPIs to improve athletes` performance by enhancing reflective thinking as well as pre-reflective awareness. Furthermore, we discuss the epistemological and practical considerations regarding the selection and use of activity traces in SCMPIs. The paper calls for further research to evaluate the SCMPI's impact on performance in elite athletes, emphasizing the need for a rational application of this method in both research and practical interventions.